STRATEGI PEMASARAN TERBAIK DESTINASI WISATA THEME PARK JUNGLE FESTIVAL - Tatik Sriwulandari; Damas Aryo Anggoro (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2020)
Tourist destinations with the theme park concept are one form of amusement park destinations that can be one of the financial resources, driving the economy and contributing to the sustainability of goals in many fields, including investment in infrastructure, job creation, tax revenue, tourism income, donations, and community support. The Bogor Jungle Festival is one of the tourist destinations with a theme park concept that has great potential to increase the local revenue of the city of Bogor. Decreasing the number of tourists that occur will lead to reduced competitiveness and loss of potential to maximize the original goal. Therefore the right marketing strategy is needed in an effort to increase the number of tourist visits. The purpose of this study was to design the best marketing strategy based on the proposed results of discussions with several experts related to research in an effort to increase the visit of Bogor JungleFest tourists. The research design in this study used a descriptive qualitative method with a combination of mathematical calculations using Expert Choice 11 software and MS Excel as a primary data analysis tool. The analytical method used is AHP (Analytical Hierarchy Process) involving 5 appropriate expert respondents, who have sufficient knowledge, experience and insights to assess the problems under study and SAST (Strategic Assumption Surfacing and Testing) to be the method chosen to determine assumptions the basis that must be considered in determining the marketing strategy of the Bogor JungleFest park. The results showed that the highest weighting value for each level in the Hierarchy Model in this study was JungleFest Management on Actor criteria of 0.588, for sub criteria factors namely Institutional was assessed by respondents as the most influential factor in determining JungleFest Bogor's best marketing strategy with the value of the weight is 0.354. In terms of sub-criteria of activities, Capacity Building Managers are the most important activities in terms of implementing the JungleFest Bogor marketing strategy with a weight value of 0.355 while for the best strategy chosen with a value of 0.364 is Digital Marketing. The conclusion of this study is the superior strategy chosen for the best marketing of JungleFest Bogor is the Digital Marketing strategy, while the results of identification of assumptions that support the success of the marketing strategy of JungleFest Bogor are Support facilities and infrastructure, Commitment to management of Jungle Festival management and Product Diversification.